Transforming public relations practices in the digital age: A case study of the role of AI influencer Arbie Seo - Nur'aeni Nur'aeni; Dasrun Hidayat; Gita Melati (Asosiasi Pendidikan Tinggi Ilmu Komunikasi (ASPIKOM), 2025)
Digital transformation has brought significant changes in Public Relations (PR) practices, including the emergence of the phenomenon of AI influence that is influencing the way organizations build relationships with the public. This study aims to explore the role of AI influencers in PR communication strategies through a case study of Arbie Seo, one of the AI influencers active on social media. The method used is qualitative with a constructivism paradigm, involving eight informants who were deliberately selected, consisting of practitioners, academics, and PR students. The data was obtained through in-depth interviews and analyzed thematically. The results show that AI influencers play a strategic role in improving the effectiveness of communication with audiences through interactive, personalized, and data-driven approaches. However, there are obstacles in the integration between technology and the human element, especially in the context of empathy and credibility. Therefore, collaboration between human communication expertise and AI technology capabilities is essential to achieve a sustainable communication strategy. This research makes a theoretical contribution by enriching digital PR literature and emphasizing the importance of technological adaptation in the PR profession. Practically, the results emphasize the need for PR actors to be ready to respond to changes in the communication landscape due to the development of artificial intelligence technology.